Post-Colonial Discourse in Achebe's Things Fall Apart - Chapagaee, Rajendra Prasad (Interdisciplinary Journal of Management and Social Sciences, 2024)
This study aims at revealing Igbo society and the decline of its cultural identity as a result of British colonialism and the hegemony imposed through judicial, medical, educational, and church-missionary institutions. When the protagonist's son betrays his father and the brothers ridicule the concept of brotherhood by becoming Christians, the peaceful Igbo community gets turned into anarchy. The harmony of the Igbo community was destroyed by the effects of colonialism and the supremacy of European culture. Consequently, the rich cultural heritage collapses and crumbles despite constant resistance and sacrifice of a sincere lover of native culture. Post-colonial social narrative, a narration of society, postulates the issues of presentation, expression and evocation of a community which is preliminarily structured by a number of cultural ethos, now it has been contaminated by colonial power. The community experiences a significant transformation while the true followers original culture struggle with the shifting dynamics of relationships. European civilization interferes and challenges the traditional way of life of the Igbo people. Identity of the indigenous people gets reshaped as they fight against the changes imposed by the colonists.